Fertilizer use optimization in sub-Saharan Africa - Wortmann, Charles S. (CABI, 2017)
This book contains 17 chapters providing details on decision tools that use linear programming to determine recommendations specific to a farmer's context intended to maximize profit from fertilizer use in sub-saharan Africa. Chapter 1 and 2 discusses the principles and approach, and spatial analysis of fertilizer use optimization, respectively. Chapter 3 covers integrated soil fertility management in sub-Saharan Africa. Further, Chapters 4 to 16 explore optimizing fertilizer use within an integrated soil fertility management framework in countries in sub-Saharan Africa, including: Burkina Faso, Ethiopia, Ghana, Kenya, Mali, Malawi, Mozambique, Niger, Nigeria, Rwanda, Tanzania, Uganda, and Zambia. Finally, Chapter 17 describes the process of enabling fertilizer use optimization in sub-Saharan Africa.